Multi-body Dynamic Analysis of the Braking Process for Megawatt Wind Turbine Disc Brake. (January 2019) - Zhang, S; Xue, C; Yin, J; Sha, Z; Ma, F; Yang, D; Liu, Y
Abstract: The dynamic characteristics of brake during the braking process are studied by the method of multi-body dynamics, in order to reduce the vibration of disc brake in the emergency braking process, improving the braking efficiency of the brake of the megawatt wind turbine. The flexible multi-body dynamics model of the mechanical assembly for the whole megawatt wind turbine disc brake is built, including the brake spring, active brake caliper, passive brake caliper and compensatory mechanism. The simulation results under the common working conditions are compared with the test results under the same working condition to verify the model. The influence trends of braking parameters, such as initial braking speed, spring braking force and friction coefficient between the brake pairs, on the dynamic characteristics of the brake are analyzed, which provides the theoretical basis for reducing the severe vibration during the emergency braking process in this paper.